Training with a peripheral intravenous catheter care algorithm to affect phlebitis and infiltration incidence: An interventional, before and after study - Erdogan, Banu Cihan; Baykara, Zehra Gocmen (Australian journal of advanced nursing, 2024)
Objective: This study attempted to determine the effect of training with a peripheral intravenous catheter care algorithm on nurses' knowledge level and the incidence of phlebitis and infiltration. Background: Peripheral intravenous catheter insertion is a common nursing intervention for hospitalised patients. However, it causes many complications, of which phlebitis and infiltration are the most prevalent. Many factors affect the development of phlebitis and infiltration. Study design and methods: This study was an interventional and cross-sectional -before and after study. This study was conducted with 19 nurses and 190 patients (who had 297 peripheral intravenous catheters). After the Peripheral Intravenous Catheter Care Algorithm was developed, the study was conducted in three stages: the prevalence of phlebitis and infiltration and the knowledge level of nurses before intervention was evaluated during the first stage; training and consultancy services were provided during the second; and the incidence of phlebitis and infiltration and the knowledge level of nurses after intervention was evaluated in the last stage. Results: The nurses median scores regarding the knowledge test on phlebitis and infiltration improved significantly after their training. Despite the incidence of phlebitis decreasing after the training, it was not statistically significant. However, the grade of phlebitis proved significantly lower after the nurses’ training. Furthermore, the incidence and grade of infiltrations decreased after training, but it was not statistically significant either. Conclusion: It can be concluded that training with the Peripheral Intravenous Catheter Care Algorithm is effective in increasing the nurses’ knowledge and reducing the grade of phlebitis. Accordingly, training nurses with the Peripheral Intravenous Catheter Care Algorithm, based on clinical guidelines, is recommended. Implications for research, policy, and practice: An algorithm has been developed in this study to guide hospitals in clinics where peripheral intravenous catheter is applied. This is noteworthy that by preventing these complications, patients can be prevented from receiving treatment (medical treatment, surgical repair etc.) for complications, prolonged hospital stay, stress in patients and their relatives, increased workload of healthcare personnel, and increased health expenditures can be avoided by preventing these complications.